2015
DOI: 10.1111/eea.12331
|View full text |Cite
|
Sign up to set email alerts
|

Divergence and evolution of reproductive barriers among three allopatric populations of Rhagoletis cingulata across eastern North America and Mexico

Abstract: Geography is often a key factor facilitating population divergence and speciation. In this regard, the geographic distributions of flies in the genus Rhagoletis (Diptera: Tephritidae) in temperate North America have been affected by cycles of Pleistocene glaciation and interglacial periods. Fluctuations in climatic conditions may have had their most dramatic effects on geographically isolating Rhagoletis flies in the central highland region of Mexico. During past periods of allopatry, a degree of post‐zygotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 59 publications
1
42
0
Order By: Relevance
“…Average (±SE) duration (days) corrected for artificial winter length (by substracting the total number of days held at 5°C according to treatment) from pupation to adult eclosion of three species of Rhagoletis fruit flies and their parasitoids. These 'populations' exhibited significant differences in the time from fruit collection to adult eclosion under uncontrolled environmental conditions in central Mexico (Xalapa), and were found to be reproductively isolated (Tadeo et al, 2015). Here we found that under similar environmental conditions, two of these populations (central and norteastern Mexico) differ in duration of dormancy.…”
Section: Discussionmentioning
confidence: 59%
“…Average (±SE) duration (days) corrected for artificial winter length (by substracting the total number of days held at 5°C according to treatment) from pupation to adult eclosion of three species of Rhagoletis fruit flies and their parasitoids. These 'populations' exhibited significant differences in the time from fruit collection to adult eclosion under uncontrolled environmental conditions in central Mexico (Xalapa), and were found to be reproductively isolated (Tadeo et al, 2015). Here we found that under similar environmental conditions, two of these populations (central and norteastern Mexico) differ in duration of dormancy.…”
Section: Discussionmentioning
confidence: 59%
“…New microsatellite and mtDNA sequencing data in the current study were generated from three non-cherry-infesting populations of R. cingulata group flies: R. chionanthi (site 18, collected from fringe-tree at Perry, Georgia), R. osmanthi (site 19, collected from tea-olive at Lake Lizzie, Florida), and R. turpiniae (site 20, collected from muttonwood at Xalapa, Veracruz, Mexico). Flies were reared to adulthood in the laboratory using standard Rhagoletis husbandry methods [41], as described in Feder et al [42] and Tadeo et al [43]. Specimens were frozen and stored at −80 °C prior to genetic analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Crosses testing for intrinsic postzygotic RI were performed as described in Tadeo et al [43]. Rhagoletis cingulata collected as larvae infesting black cherry fruit from South Bend, IN and R. indifferens infesting sweet cherries in Vancouver, WA in 2015 were transported to the University of Notre Dame, Notre Dame, IN, where they were reared to adulthood following a five-month overwintering period as pupae.…”
Section: Methodsmentioning
confidence: 99%
“…With the advent of molecular techniques, research on fruit flies advanced our understanding of mixed models of speciation, in particular those involving speciation with gene flow (Feder et al, 2003). Experimental hybridization studies and molecular data revealed that several Rhagoletis species in the pomonella, suavis, and cingulata species groups potentially interbreed, leading in some cases to speciation and adaptive introgression (Schwarz & McPheron, 2007;Rull et al, 2010;Arcella et al, 2015;Tadeo et al, 2015). In general, many more animal species are likely exchanging genes than has been previously appreciated, with some groups exhibiting greater frequency of introgression than others (Mallet et al, 2016).…”
Section: Introductionmentioning
confidence: 99%